Brinquedos e Brincadeiras de Ontem e Hoje - Bernhardt , Cristiane Otilia Colossi; Moreira , Iris Vania Aparecida; Alencar , Rosania Aparecida de Souza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf